Digital art - Paul, Christiane (World of art, 2015)
Digital technology has revolutionized the way we produce and experience art today. Not only have traditional forms of art such as printing, painting, photography and sculpture been transformed by digital techniques and media, but entirely new forms such as internet art, software art, digital installation and virtual reality have emerged as recognized artistic practices. Christiane Paul surveys the developments in digital art from its appearance in the 1980s to the present day and looks ahead to what the future may hold. Drawing a distinction between work that uses digital technology as a tool to produce traditional forms and work that uses it as a medium to create new types of art, she discusses the key artists and works. The book explores themes addressed and raised by these artworks, such as viewer interaction, artificial life and intelligence, political and social activism, networks and telepresence, and issues surrounding the collection, presentation and preservation of digital art. This third, expanded edition investigates key areas of digital art practice that have gained in prominence in recent years, including the emergence and impact of locative media, interactive public installation, augmentive and mixed reality, social networking, and file-sharing and tablet technologies